Analisis Laporan Arus Kas pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Bekasi Tahun Anggaran 2018-2020 - Siti Hasanah; Khaerul Umam; Fitri Pebriani Wahyu (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
The purpose of this study is to find out how the state of cash flow in the cash flow statement in the Bekasi City Government during 2018-2020. The Cash Flow Statement is made to find out the movement of cash real money from the beginning of the year to the end of the year, in addition to knowing how much cash is used, and to find out one year of cash operation used for anything. In this study, the research method used is descriptive qualitative with the focus of the object being the Bekasi City Government, especially in the Regional Financial and Asset Management Agency (BPKAD) as the body tasked with managing assets contained in local governments and preparing financial reports. The official website of the Bekasi City Government is the secondary data used in this study. The results of this study showed that overall cash flow growth in 2018-2020 from operating activities, investment activities and financing activities showed that the state of financial performance in the Bkeasi City Government was not good and from the analysis of free cash flow obtained results in 2018-2020 there was a decrease in free cash flow which decreased as the existence of decreased free flow indicated that the Regional Government had financial difficulties.Keywords : operating activities, investment activities and financing activities